Digitalization of Government Think Tanks in Nigeria - Adeyinka Patrick Adewumi (Universitas Medan Area, 2022)
The shift to industry 4.0, characterized by advanced technologies, necessitates government agencies' digital transition, presently at a marginal level in Nigeria, of which policy think tanks are also victims. Think tanks in Nigeria are saddled with the responsibility of producing policy recommendations through research in response to vast and intricate societal problems. These responsibilities, given global technological advancements and its relevavnce to policy research require technological aid to probe and suggest accurate, responsive policy advice to the government. To this end, this paper aims to examine the state of digitalization and re-echo the need for the digital transition of skills, personnel, and equipment at the Nigerian Institute of Social and Economic Research (NISER) to enable the production of solution-oriented outputs through which responsive policy recommendations can be made. This study relies on a descriptive methodology, using primary and secondary data from information gathered from the Institute through participant observation and in-depth interviews and the internet. The findings reveal that in NISER, there is growing adoption and transition towards digital transformation; however, there are still concerns about the practicability of the process, which as a result, impedes general productivity. This study recommends digital investment through adequate finance and digital infrastructure support from the government into NISER to reap the benefits of improved productivity and efficiency.